The heme auxotroph Caenorhabditis elegans can cleave the thioether bonds of c‐type cytochromes. Issue 6 (1st March 2018) - Murphey, Annie C.; Mavridou, Despoina A. I.; Hodgkin, Jonathan; Ferguson, Stuart J.
Abstract : Heme is essential and synthesized via highly regulated processes. For this reason, most organisms strive to recycle it or acquire it from their environment. When heme is bound to proteins noncovalently, degradation of the polypeptide is sufficient to release it. However, in some hemoproteins, such as c ‐type cytochromes, heme is covalently bound to the protein backbone. We use the heme auxotroph Caenorhabditis elegans to investigate if cytochromes c can be a heme source, and we show that this organism must encode a novel system which specifically cleaves the thioether bonds of c ‐type cytochromes. We also find that at limiting heme concentrations, while somatic tissues develop normally the germline fails to proliferate, suggesting the presence of a heme‐sensing checkpoint in C. elegans . Abstract :